Artificial Intelligence As A Multipurpose Tool For Writing Engagement In Efl Learning Context: Writing Accuracy And Learners’ Perspective - Fitri, Riana Annisa (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2024)
The objective of the research is to find out Learners' Perspective about Artificial Intelligence if their writing accuracy.  This study was conducted at the Universitas Muhammadiyah Sumatera Utara, especially for students from the English education study program. The study was designed to assess the impact of AI on the writing accuracy of use AI writing tools, providing valuable insights for educators, developers, and policymakers seeking to optimize AI technologies to support EFL learners in writing their writing text and language learning endeavors. The results of the study showed that AI-powered writing tools can help learners improve their writing skills in several ways: Grammar and Spelling Correction, Style and Clarity Enhancement, Vocabulary and Language Enrichment, Plagiarism Detection, Language Proficiency Assessment, and Personalized Learning Experience (Gayed et al., 2022). As a result, students believe that the AI writing tool paradigm meets their writing needs and helps their writing become better and more accurate.